The Influence of Financial Literacy and Government Financial Support on the Financial Performance of Micro Businesses: the Mediating Role of Access to Finance - Setyawati, Amelia (International Journal of Business, Law, and Education, 2025)
This study aims to analyze the effect of financial literacy and government financial support on financial performance, with access to financing as a mediating variable. A quantitative approach was used in this study, with Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis techniques processed using SmartPLS 4 software. The research population included micro-businesses in the agribusiness sector in Batu City, with a sample size of 383 agribusiness entrepreneurs residing in the region. The findings show that both access to financing and government financial support have a positive and significant effect on financial performance. Conversely, financial literacy does not have a significant direct impact on financial performance. However, access to financing was found to mediate the relationship between financial literacy and government financial support with financial performance. These results provide policy recommendations to improve the financial performance of micro businesses by increasing financial literacy and strengthening government financial support, by expanding access to sources of financing—thereby ultimately improving the welfare of micro entrepreneurs.